ТҮРКИЙ ТИЛЛЕРИНЕ ОРТАҚ ЖӘМИЙЕТЛИК-СИЯСИЙ ЛЕКСИКА - Нажимов, А.Ш. (SCIENCE and SOCIETY, 2021)
The article expands the circle of words belonging to the layer of identity in the system of socio-political vocabulary, depending on social factors in the literary language, state structure, social conditions, historical changes. It is known that most of the words specific to Turkic languages are common or broad in the native languages. This is probably why the words related to the main layer were analyzed on the basis of the concepts of the common Türkic vocabulary, the common Türkic layer.
Keywords: public; political vocabulary; kalpak; black hoods; statehood; written records; terminology; history of language development